Overcrowding and Stress Levels among Female Prisoners: A Cross-Sectional Study - Rabbani, Hasna; Hidayati, Nur Oktavia (Jurnal Keperawatan Soedirman, 2024)
Overcrowding is when the number of people in a space exceeds its specified capacity. This phenomenon often occurs in prisons and has been recognized as a significant contributor to psychological problems, especially stress among prisoners. This study addresses this gap by narrowing our focus to female prisoners, who exhibit greater physical and psychological vulnerabilities than male prisoners. This study investigates the relationship between overcrowding and stress levels in prisoners. This study used a correlational design with a sample of 82 female prisoners selected using a simple random sampling technique. The Overcrowding Scale and the Perceived Stress Scale-10 were the standardized instruments used in this study. Data were analyzed using Rank Spearman. The analysis revealed a positive relationship between overcrowding and stress levels with p = 0.000 and r = 0.415. Therefore, nurses can provide education to minimize the prisoners’ stress levels, and prison officers can improve prisoner fulfillment of psycho-socio-spiritual needs. Future comparative studies can be conducted across various prison facilities to identify variations in stress levels, assess the effectiveness of interventions, and explore sociocultural influences on the well-being of prisoners.